Kedudukan Hukum Sema No. 3/2015 terhadap Putusan UU No. 35/2009 Tentang Narkotika Berdasarkan Hierarkis Perundang-Undangan di dalam Memutus Perkara Narkotika - Hendra Catur Putra; Ulya Kencana; Duski Duski (Universitas Batanghari Jambi, 2022)
Study on the juridical analysis of SEMA No. 3 of 2015 on the Decision of the Narcotics Law Number 35/2009 based on a hierarchical law with legal certainty is very necessary. The number of narcotics cases was decided as a crime of drug abuse, example of the decision of the narcotics case in the Lahat District Court, where the Panel of Judges sentenced based on Article 112 paragraph (1) of Law 3/2009 and the demands of the Public Prosecutor. His sentence was only ten months. far above the minimum sentence stated in Article 112 paragraph (1), which is four years according to SEMA 3/2015, where the judge may decide narcotics cases below the minimum. This violates the principle of